2014
DOI: 10.12965/jer.140092
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise ameliorates symptoms of attention deficit/hyperactivity disorder through reducing Purkinje cell loss and astrocytic reaction in spontaneous hypertensive rats

Abstract: Attention deficit/hyperactivity disorder (ADHD) is a neurobehavioral disorder of cognition. We investigated the effects of treadmill exercise on Purkinje cell and astrocytic reaction in the cerebellum of the ADHD rat. Adult male spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKYR) weighing 210± 10 g were used. The animals were randomly divided into four groups (n= 15): control group, ADHD group, ADHD and methylphenidate (MPH)-treated group, ADHD and treadmill exercise group. The rats in the MPH-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Studies showed deficits in executive functions such as spatial working memory and attention, as well as locomotor impairments due to reduction of cerebellar volume in SHRs (Yun et al 2014). However, when the decline of locomotor activity is accounted for, SHRs performed significantly better than controls (Sontag et al 2013).…”
Section: Cerebral Small Vessel Disease Modelmentioning
confidence: 98%
“…Studies showed deficits in executive functions such as spatial working memory and attention, as well as locomotor impairments due to reduction of cerebellar volume in SHRs (Yun et al 2014). However, when the decline of locomotor activity is accounted for, SHRs performed significantly better than controls (Sontag et al 2013).…”
Section: Cerebral Small Vessel Disease Modelmentioning
confidence: 98%
“…30 Yan et al found that treadmill exercise might exert ameliorating effect on neurodevelopmental disorders by decreasing the rate of Purkinje cell loss in the cerebellum. 31 Therefore, SPARK program which consist of activities requiring learning skills, motor control and social engagement, positively improves cortical, sub-cortical and cerebellar function. Although, in the present study, there is no direct measurement for cerebellar function, the results and findings of studies related to neurological base support our interpretation.…”
Section: Groupsmentioning
confidence: 99%
“…Traits that are often observed in individuals with ADHD, such as shorter attention spans, inability to focus, and hyperexcitability, are also observed in the SHR, making it an ideal model to investigate the etiology of ADHD (Adriani et al, 2003). Similar to individuals with ADHD, SHRs are also characterized by cerebellar atrophy and cerebellar impairment (Yun et al, 2014). Evidence of a greater incidence of learning disabilities has also been reported in children with ADHD diagnosed with primary hypertension than in those without (Adams et al, 2010).…”
Section: Brain Ras and Neurologic Disordersmentioning
confidence: 99%